2008
DOI: 10.1186/1742-4690-5-53
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi (Chagas' disease agent) reduces HIV-1 replication in human placenta

Abstract: Our results demonstrated that the presence of an intracellular pathogen, such as T. cruzi, is able to impair HIV-1 transduction in an in vitro system of human placental histoculture. Direct effects of the parasite on cellular structures as well as on cellular/viral proteins essential for HIV-1 replication might influence viral transduction in this model. Nonetheless, additional mechanisms including modulation of cytokines/chemokines at placental level could not be excluded in the inhibition observed. Further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…In this regard, it has been shown that IL-6, IL-8, IP-10 and MCP-1, which downmodulate T. cruzi replication [22], are diminished in human placental histocultures co-infected with HIV and T. cruzi, as well as in those stimulated with parasite-shed/-secreted factors. However, T. cruzi inhibits HIV replication at the placental level [23]. Similar results were observed in primary human monocyte-derived macrophages (MDMs), where HIV replication was inhibited by both free trypomastigotes and trypomastigote soluble factors.…”
Section: Key Pointssupporting
confidence: 55%
“…In this regard, it has been shown that IL-6, IL-8, IP-10 and MCP-1, which downmodulate T. cruzi replication [22], are diminished in human placental histocultures co-infected with HIV and T. cruzi, as well as in those stimulated with parasite-shed/-secreted factors. However, T. cruzi inhibits HIV replication at the placental level [23]. Similar results were observed in primary human monocyte-derived macrophages (MDMs), where HIV replication was inhibited by both free trypomastigotes and trypomastigote soluble factors.…”
Section: Key Pointssupporting
confidence: 55%
“…We recently reported that T. cruzi inhibited HIV replication in human chorionic villi histocultures and in a trophoblast cell line. The study suggested that coinfection with T. cruzi may have a deleterious effect on HIV-1 transduction and thus, it could play an important role in viral outcome at the placental level [26]. Here, we have conducted studies of HIV/ T. cruzi co-infection in their common cellular target: human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The role of such microbiota on the transmission of congenital infection, and more specifically the role of its bacterial composition on the capacity of T. cruzi to infect placental cells (trophoblast, fibroblasts, Hofbauer-, smooth muscle-, amniotic-and endothelial-cells) deserve further investigations. In connection with this new potential ecological association with congenital Chagas disease, it is of interest to note that previous observations reported that T. cruzi reduces HIV-1 replication in human placenta (Dolcini et al, 2008).…”
Section: Interpretation Attempt Of T Cruzi-placenta Interactionsmentioning
confidence: 98%